The Impact of NO2 and SO2 Pollutants on Respiratory Diseases: A Case Study of Indonesia - Reizka Asadelia Rafmawan (Eduvest - Journal of Universal Studies, 2026)
Air pollution remains a significant public health challenge in Indonesia, driven by rapid industrialization and urbanization. Key pollutants such as NO₂ and SO₂ are strongly linked to respiratory conditions, yet comprehensive national evidence on their age-specific impacts remains limited. This study aims to examine the causal effects of NO₂ and SO₂ exposure on the incidence of acute respiratory infections (ARI), pneumonia, and asthma in Indonesia, with a particular focus on differences across age groups. This study employs a quasi-experimental design using district-level pollution data and individual health data from Riskesdas 2018. Analysis was conducted via multiple linear regression, coefficient stability testing, and IPW to estimate robust causal associations. Age-stratified analysis was performed across five groups: 0–4, 5–17, 18–49, 50–74, and 75+ years. Results show that NO₂ exhibits a strong positive association with ARI incidence, particularly among children aged 0–4 and 5–17 years, and is linked to asthma in adults aged 18–49. SO₂ shows significant positive effects on ARI among older adults (50–74 years) and on asthma in those aged 75 and above. However, unexpected negative or non-significant relationships were found between NO₂ and pneumonia/asthma, and between SO₂ and certain outcomes, likely reflecting data constraints and unobserved confounders. In conclusion, this study reveals age-specific pollutant–health relationships and underscores the need for targeted air quality interventions. Recommendations include strengthening monitoring systems, implementing pollutant-specific warnings, and integrating environmental–health data to support evidence-based policies and protect vulnerable groups.